2017
DOI: 10.1016/j.ygyno.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Why does cervical cancer occur in a state-of-the-art screening program?

Abstract: Background The goal of cervical screening is to detect and treat precancers before some become cancer. We wanted to understand why, despite state-of-the-art methods, cervical cancers occur related to programmatic performance at Kaiser Permanente Northern California (KPNC), where >1,000,000 women aged ≥30 years have undergone cervical cancer screening by triennial HPV and cytology cotesting since 2003. Methods We reviewed clinical histories preceding cervical cancer diagnoses to assign “causes” of cancer. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Numerous studies from around the world have found non-attendance at screening to be a key reason for the development of cancer despite the availability of cervical screening [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Castle et al [ 24 ] recently described the screening histories of 623 women diagnosed with cervical cancer aged ≥30 yrs. in 2003–15 in one integrated health care system (Kaiser Permanente Northern California; KPNC) in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies from around the world have found non-attendance at screening to be a key reason for the development of cancer despite the availability of cervical screening [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Castle et al [ 24 ] recently described the screening histories of 623 women diagnosed with cervical cancer aged ≥30 yrs. in 2003–15 in one integrated health care system (Kaiser Permanente Northern California; KPNC) in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…At KPNC, during the time of this analysis, women were tested by HC2 to triage equivocal cytologic results of atypical squamous cells of undetermined significance (ASC-US) (since 2001) and as a cotest with cytology for women aged 30 years and older (since 2003) (24)(25)(26). Recent KPNC protocol changes to start cotesting at age 25 were not considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The KPNC/NCI guidelines cohort has been previously described. 3 Starting in 2003, women 30 to 65 years old were routinely co-tested with Hybrid Capture 2 (HC2) and cytology. The current analysis includes histopathologic end point data for women aged 25 to 77 years through 2015, comprising more than a million women's outcomes.…”
Section: Methodsmentioning
confidence: 99%